THE EFFECT OF DIGITAL MARKETING, DEMOGRAPHY, AND HUMAN RESOURCES COMPETENCY ON THE MARKETING PERFORMANCE OF THE UPPKS GROUP OF BERGAS SUB-DISTRICT IN THE TIME OF COVID-19 RECOVERY - Tri Imaliya; Edwin Zusrony; Adi Suryo Ramadhan; Azzahro Uswatun Nisa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this research is to determine the impact of digital marketing, demographic factors, and human resource competencies on the marketing performance of UPPKS Bergas sub-district, Semarang district, during the COVID-19 recovery period. Ex post facto quantitative methods are used in the research design. Five UPPKS were used by the population, totaling 50 employees. A simple random sampling technique was used in this study. The research data is derived from primary data sources, such as questionnaires and observations, as well as secondary data sources, such as related documents. Digital marketing, demographic factors such as gender and age, HR competencies, and marketing performance are the research variables. The data was analyzed using classical assumption tests and hypothesis tests in the form of T tests and F tests, which were aided by the SPSS program. The outcomes of the analysis show that: (1) digital marketing has a significant effect on marketing performance with a significance value of 0.014 in the low category; (2) gender has a significant effect on marketing performance with a significance value of 0.015; (3) age has a significant effect on marketing performance; (4) HR competencies has a significant effect on marketing performance with a significance value of 0.038 in the low category; and (5) all variables combined have a significant effect on marketing performance.